2020
DOI: 10.1590/0102-33062019abb0297
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank in a subtropical grassland under different grazing intensities

Abstract: Grazing is an important determinant for the composition and structure of grasslands; however, soil seed bank (SSB) response to grazing intensity is poorly investigated. We analyzed SSB richness and density in a subtropical grassland in southern Brazil with different forage offers (low, intermediate, high and very high), that is, contrasting grazing intensities. The SSB was evaluated by the seedling emergence method. We collected ten SSB samples at two layers (0-5 and 5-10 cm) in spring and autumn in each of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
3
3
0
Order By: Relevance
“…Previous studies showed that overgrazing can increase SSB density through seed production of a few annuals (Erfanzadeh et al, 2020; Franca et al, 2018). In agreement with our findings, a positive correlation between SSB density and grazing intensity was observed in Silva and Overbeck (2020) study. They demonstrated that when grazing pressure is low, a high cover of perennial grasses and a large SSB of these grasses may be present, whereas annual grasses with their seeds in the soil appear with increasing grazing.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that overgrazing can increase SSB density through seed production of a few annuals (Erfanzadeh et al, 2020; Franca et al, 2018). In agreement with our findings, a positive correlation between SSB density and grazing intensity was observed in Silva and Overbeck (2020) study. They demonstrated that when grazing pressure is low, a high cover of perennial grasses and a large SSB of these grasses may be present, whereas annual grasses with their seeds in the soil appear with increasing grazing.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, we can infer that for our studied areas the speed of the post-disturbance recovery represented a vegetation property inherent to the successional stage in which it is found. The lack of influence of the seed bank in our study reinforces what other studies Overbeck 2020, Silva and have already evaluated for the region regarding this vegetative component quality.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, increased seed input to the seed bank by annuals caused the transient seed bank to increase with increased grazing disturbance after the threshold. In addition, overgrazing of the dominant plant species by livestock reduces the competitiveness of dominant populations and allows populations of some non‐dominant species to increase rapidly, consequently increasing their seed density in the soil seed bank (Ma et al, 2010; Silva & Overbeck, 2020). Hence, the transient seed bank showed a decreased and increased with increased grazing disturbance before and after the threshold, respectively.…”
Section: Discussionmentioning
confidence: 99%